1981
DOI: 10.1172/jci110057
|View full text |Cite
|
Sign up to set email alerts
|

The chronically instrumental ewe: a model for studying vascular reactivity to angiotensin II in pregnancy.

Abstract: A B S T R A C T Vascular refractoriness to the systemic pressor effects of angiotensin II (AII) develops normally during human pregnancy. To ascertain if the ewe might provide a suitable anfomal model to study the mechanisms responsible for this response (unique to pregnancy) we studied this phenomenon in unanesthetized, chronically instrumented nonpregnant and pregnant sheep, 68-143 d gestation. In these studies dose-response curves were established for changes in both mean arterial pressure and uterine blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 19 publications
8
42
1
Order By: Relevance
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 68%
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 68%
“…Normal pregnancy is associated with the development of relative vascular refractoriness to the systemic pressor effects of infused angiotensin II (ANG II)' in women (1)(2)(3), sheep (4,5), and several other species (6,7). This refractoriness is lost in women who develop pregnancy-induced hypertension (preeclampsia), and they become exquisitely sensitive to the pressor effects of infused ANG 11 (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the chronically instrumented sheep may serve as an excellent animal model in which to study the normal cardiovascular changes that occur in pregnancy (5,15). In these studies, the uterine vascular bed of late pregnant sheep was even less responsive to infused ANG II than the systemic vascular bed overall (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, pregnant women destined to develop preeclampsia lose this refractoriness and become increasingly sensitive to the pressor effects of infused ANG II (4); however, the mechanism(s) responsible for these changes is unknown. The pregnant ewe (5,6) and several other species (7, 8) also develop attenuated pressor responses to infused ANG II. Moreover, the dose ofANG II required to elicit a 20-mmHg rise in mean arterial pressure in pregnant and nonpregnant ewes is virtually identical to that required in normotensive pregnant and nonpregnant women, respectively (3)(4)(5).…”
mentioning
confidence: 99%